Kepatuhan Diet dengan Kualitas Hidup Pasien Hemodialisa di RSUP Dr. Soeradji Tirtonegoro: Korelasi Studi - Heru Ginanjar Triyono; Dian Novita K; Sugiarto Sugiarto; Tengku Isni Yuli; Winda Rofiyati (Wiraraja Medika : Jurnal Kesehatan, 2020)
Abstract Kidney is one the organs that has an important function in the body. These functions include regulating the concentration of salt in the blood, and regulating the balance of acid base and the excretion of excess salt.Design Of this study was analytic with total Random Sampling. Research that uses descriptive quantitative type using cross sectional. This researcher only observed and measured variables without giving treatment. Cross sectional design or cross-sectional study, researchers only make observations and measure variables at one time. The Sampling in this study. The sampling in this study were 30 respondents who underwent hemodialysis. The amount was obtained based on data on the number of patients. The results of the analysis of the relationship of diet adherence with the quality of life of hemodialysis patients at Hospital using the chi square test. From table 4.4 the chi suare correlation test results obtained sig (2-tailed) values ​​with the results of 0.003 p value <0.05 to 0.003 <0.05 showed a relationship between diet compliance with quality of life. Data generated from the bivariate analysis of respondents who comply with good quality of life were 14 respondents (66.7%), while respondents who were not compliant and with less quality of life were 4 respondents (44.4%). Key word: Diet, Kidney Failure, Quality Of Life, Hemodialysis